Factors associated with oral hygiene practices among adults with systemic sclerosis. Issue 3 (15th October 2013) - Yuen, HK; Hant, FN; Hatfield, C; Summerlin, LM; Smith, EA; Silver, RM
Abstract Objective To identify factors associated with oral hygiene practices in adults with systemic sclerosis (SSc). Methods In this cross‐sectional study, 178 dentate adults with SSc received an oral examination which included measurement of oral aperture, assessment of manual dexterity to perform oral hygiene, as well as completion of the Center of Epidemiological Studies Depression (CES‐D) Scale and an oral health‐related questionnaire. Results Multivariable logistic regression modelling showed male, minority and high CES‐D scores (i.e. clinically significant symptoms of depression) were associated with less likelihood of participants brushing teeth at least twice daily, but the presence of self‐reported dry mouth symptoms increased the likelihood of toothbrushing. Having a dental visit in the past 12 months and use of an adapted flossing or interdental cleaning device were significantly associated with daily dental flossing; however, having difficulty flossing teeth reduced the likelihood of daily flossing. Conclusions Overall, demographic variables were strongly associated with toothbrushing frequency, whereas flossing self‐efficacy and barriers were strongly associated with dental flossing frequency in adults with SSc. The results suggest that dental health professionals should take mental health into consideration when educating patients with SSc to improve their oral hygiene and consider making referrals for patients exhibiting suspected clinically significant depressive symptoms to mental health professionals for further evaluation and treatment. In addition, an appropriate adapted flossing or interdental cleaning device should be recommended to increase dental flossing practices in this patient population.